Kinematic study of a vehicle on the Tazón restrained ramps - Falcón Veloz, Nelson (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
In the present paper the restreined ramps are revised under kinematic conditions. More specifically, the Tazón restrained ramp in the Coche-Tejerías freeway, near Caracas (Venezuela). This kinematic study show that, in their energy disipators, the longitud and friction coefficient is not enough to break cars, and present an inadequate road design. New conditions above friction coefficient, contrapendent and longitud are shown and maybe employed in other restrained ramps in freeways.